Refractive errors among first year undergraduate University students / Nur Amalina Abdul Khalid - Abdul Khalid, Nur Amalina (2016)
Background: Refractive error is described as common eye disorder which the optical imperfections that prevent the eye from properly focusing the light on the retina and causing blurred vision. The prevalence among international university students was high. However, no data on prevalence of Malaysia university students reported. Aim: The aim of this study is to determine the prevalence of refractive errors among 1st year university students in UiTM Selangor Puncak Alam Campus by using Logarithm Minimum Angle of Resolution Test (LogMAR). Method: A total of 200 subjects of first year undergraduates students were included in this study. Unaided and aided visual acuity were taken using LogMAR chart. The subjective refraction was done by using the standard procedure. Result: The prevalence of refractive error among first year undergraduates students in UiTM Selangor Puncak Alam Campus was myopia SE < -0.50D (63.5%) and emmetropia SE±0.50D (33.0%). The unaided visual acuity among first year undergraduates students was < 6/60 (29.0%). The aided visual acuity among first year undergraduates students was 6/6 (100%). Conclusion: The occurence of refractive error was found high in university students and the higher proportion were found among females.